Gardner Syndrome: case report and brief review of the literature - Cruz, Isabela Azevedo Nicodemos da; Vergílio, Fernanda Sasaki; Silva, Lorena Luryann Cartaxo da; Cruz, Gabriela Azevedo Nicodemos da (Medicina (Ribeirao Preto), 2017)
Type of study: Case report. Relevance and comments: Gardner Syndrome is a variant of Familial Adenomatous Polyposis (FAP), with the association of gastrointestinal polyps, soft tissue tumors and bone tumors. It is a rare disorder and early diagnosis is crucial to reduce its morbimortality. The present report illustrates a case of Gardner Syndrome with its clinical and radiologic features, as well as a brief review of the literature.